Associations of Serum Fatty Acid Proportions with Obesity, Insulin Resistance, Blood Pressure, and Fatty Liver: The Cardiovascular Risk in Young Finns Study - Kaikkonen Jari E; Jula Antti; Viikari Jorma SA; Juonala Markus; Hutri-Kähönen Nina; Kähönen Mika; Lehtimäki Terho; Raitakari Olli T (Oxford Academic, 2022)
Background: The links between fatty acids (FAs) and cardiometabolic outcomes are topics of debate.
Objective: Our aim was to investigate the associations between serum standardized FA percentages and cardiometabolic outcomes.
Methods: We used cross-sectional (n = 2187-2200 subjects, age 24-39 y, women 54%) and 10-year prospective data (n = 975-1414 subjects) from the Young Finns Study. Outcomes included prevalent and incident obesity, insulin resistance (HOMA-IR index in the upper quintile), elevated blood pressure (BP; taking medication, or diastolic or systolic BP in the upper quintile), and incident nonalcoholic fatty liver. Logistic regression models were used to calculate ORs per SD increase in fatty acids (FAs). The models were adjusted for age and sex, and additionally for other potential confounders.
Results: Several cross-sectional findings were also statistically significant in prospective models (Bonferroni corrected P < 0.003). In fully-adjusted models for obesity, these consisted of SFAs (OR: 1.28) and MUFAs (OR: 1.38), including palmitoleic (OR: 1.39) and oleic acids (OR: 1.37). Furthermore, PUFAs (OR: 0.70), including linoleic (OR: 0.67) and docosahexaenoic acids (OR: 0.75), were inversely related with obesity, whereas γ-linolenic acid (OR: 1.32) was positively associated with obesity. In age- and sex-adjusted models for insulin resistance, MUFAs (OR: 1.26) and oleic acid (OR: 1.25) were positively, and PUFAs (OR: 0.81), particularly linoleic acid (OR: 0.78), were inversely associated with HOMA-IR. Similarly with elevated BP, palmitic acid (OR: 1.22), MUFAs (OR: 1.28), and oleic acid (OR: 1.28) were positively associated with elevated BP, whereas PUFAs (OR: 0.77), n-6 (omega-6) PUFAs (OR: 0.79), and linoleic acid (OR: 0.77) were inversely associated. In fully-adjusted models for incident fatty liver, the most consistent predictors were high palmitic (OR: 1.61) and low linoleic acid (OR: 0.63) percentages. The n-6/n-3 (omega-3) PUFA ratio was not linked with any adverse outcomes.
Conclusions: High serum percentages of total SFAs and MUFAs and low PUFAs, but also several specific FAs, predict future unfavorable cardiometabolic outcomes in Finnish adults.